Quantification of perioperative changes in von Willebrand factor and factor VIII during elective orthopaedic surgery in normal individuals. (28th May 2013) - Kahlon, A.; Grabell, J.; Tuttle, A.; Engen, D.; Hopman, W.; Lillicrap, D.; James, P.
Summary: von Willebrand's disease (VWD) patients undergoing major surgery are prophylactically treated to promote haemostasis. There is variability in perioperative clinical practice; however, most guidelines suggest replacing the deficient factor to a level of 1.0 IU mL −1 (or 100%). A review of the literature reveals a paucity of well constructed descriptive data quantifying the changes in coagulation that occur in response to surgical stress. The aim of this study was to quantify the changes in haemostatic variables occurring in response to elective orthopaedic surgery in normal individuals. Eligible subjects >18 years of age undergoing total hip or knee replacement were recruited. Blood samples were drawn at five time points: baseline, preoperatively, 30 min after surgical incision, 30 min postoperatively, postoperative day (POD) 1. Analyses included t‐tests and repeated measuresanova . Overall 30 patients, 21 women and 9 men, with a mean age of 65 were included in the final analysis. All von Willebrand factor (VWF) variables were seen to significantly decrease intraoperatively and increase postoperatively. VWF multimers showed a statistically significant decrease in high molecular weight multimers intraoperatively and an increase postoperatively. On subgroup analysis, age, gender and anaesthesia type were significantly correlated with changes in VWF parameters. Data presented in the current study establish a physiological baseline for VWF parameters in the normal population and demonstrate mean VWF/factor VIII levels greater than 1.0 IU mL −1 intraoperatively. As such, current management in VWD patients does not appear to mimic the normal physiological response to surgery.